ANALYSIS OF THE RELATIONSHIP BETWEEN THEORY OF PLANNED BEHAVIOR AND THE PROMOTIVE BEHAVIOR OF ELDERLY HEALTH IN PANTAI LABU DISTRICT, DELI SERDANG - Masdalifa Pasaribu (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze the relationship between Theory of Planned Behavior (TPB) and the promotive behavior of elderly health in Pantai Labu District, Deli Serdang. A qualitative approach with a case study method was used to explore the role of attitudes, subjective norms, and perceived behavioral control in influencing the promotive behavior of the health of the elderly. Data was obtained through in-depth interviews, observations, and documentation with elderly participants and health workers. The results showed that positive attitudes towards healthy behaviors, such as physical activity, were quite high, but were not balanced with consistent behaviors, especially in terms of healthy eating and regular health checkups. Subjective norms from families and health workers are a significant driver, although negative influences from the environment remain. Perceived behavioral control is the main factor that determines the behavior of the elderly, where physical limitations, access to health services, and economic constraints are the main obstacles. These findings underscore the importance of comprehensive, community-based interventions to improve behavioral control and social support of older people. This research contributes to the understanding of factors that influence the promotive behavior of the elderly health and becomes the basis for the development of more effective intervention strategies.